A MIDDLE MIOCENE BALEEN WHALE FROM BELE VODE IN BELGRADE, SERBIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
There was a fauna of baleen whales (Cetacea: Mysticeti) in the Central Paratethys, a Miocene water body which covered the area of present-day Central Europe. Most of the fossil baleen whales from the Central Paratethys have been found in strata assigned to the regional Badenian age and comprise endemic forms, known only from this region. Here a new description is provided for a fragmentary skeleton of a whale found in Belgrade, Serbia, and its age context and biological aspects are discussed. This specimen, consisting of a fragmentary horizontal ramus of the mandible and eight caudal vertebrae, is tentatively identified as ?Parietobalaena sp., a globally known Miocene taxon, with related forms having been recorded earlier from the Eastern Paratethys. An early Sarmatian age (i.e., about 12.7-12.4 Ma) is proposed for the specimen. Based on epiphyseal fusion of caudal vertebrae, the specimen’s age is identified as a subadult, with a body length of around 2.5 m and an estimated adult body length around 3-3.5 m, which is extremely small for baleen whales. This find represents one of the latest records of baleen whales in the Central Paratethys and one of the latest published records of Parietobalaena-like taxa in the world.